Dehydration level detector through human urine with LED and LDR - Loniza, Erika; Catur Dhamayanti, Dewanti; Safitri, Meilia (Universitas Muhammadiyah Yogyakarta, 2021)
Dehydration is a condition where the body are lack of fluids. It is because the amount of fluid that enter in the body is less of fluid than the discharge. Dehydration is something that cannot be ignored. The high incidence of dehydration is due to the difficulty of seeing the signs and symptoms of dehydration for ordinary people. This tool is designed to handle the level of human dehydration by seeing whether the urine is normal or abnormal, whether is it mild dehydration, or severe dehydration. It can handled based on the color of the urine using a tool named Light Emitting Diode Sensor (LED) and a light dependent resistor (LDR). Tool innovation is the use of rechargeable batteries and a charger module to make it easier for users to recharge exhausted batteries. On the LCD also displays the proportion of the battery to make it easier for users to see the remaining battery weaponry. This tool is expected to be able to check the dehydration among the public in order to achieve the public health status. After the process of designing, testing, collecting and analyzing data on 15 samples and reading 20 times for each sample, the result is that the tool can work well, can measure the level of dehydration according to the human urine with an average value of 62.10. The reading results that appear on the LCD are the same or according to the level of dehydration shown on the urine color chart.